Development of Multi-Sensor Convergence Monitoring and Diagnosis Device based on Edge AI for the Modular Main Circuit Breaker of Korean High-Speed Rolling Stock - 윤병주; 김종일; 윤재영; 강정진; 홍유식 (International Journal of Advanced Culture Technology(IJACT), 2022)
This is a research thesis on the development of a monitoring and diagnosis device that prevents the risk of an accident through monitoring and diagnosis of a modular Main Circuit Breaker (MCB) using Vacuum Interrupter (VI) for Korean high-speed rolling stock. In this paper, a comprehensive MCB monitoring and diagnosis was performed by converging vacuum level diagnosis of interrupter, operating coil monitoring of MCB and environmental temperature/humidity monitoring of modular box. In addition, to develop an algorithm that is expected to have a similar data processing before the actual field test of the MCB monitoring and diagnosis device in 2023, the cluster analysis and factor analysis were performed using the WEKA data mining technique on the big data of Korean railroad transformer, which was previously researched by Tae Hee Evolution with KORAIL.